2002
DOI: 10.1016/s0014-5793(02)03416-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional screening of five PYPAF family members identifies PYPAF5 as a novel regulator of NF‐κB and caspase‐1

Abstract: PYRIN-containing Apaf-1-like proteins (PYPAFs) are a recently identi¢ed family of proteins thought to function in apoptotic and in£ammatory signaling pathways. PYPAF1 and PYPAF7 proteins have been found to assemble with the PYRIN^CARD protein ASC and coordinate the activation of NF-U UB and pro-caspase-1. To determine if other PYPAF family members function in pro-in£ammatory signaling pathways, we screened ¢ve other PYPAF proteins (PYPAF2, PYPAF3, PY-PAF4, PYPAF5 and PYPAF6) for their ability to activate NF-U … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
212
4
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(228 citation statements)
references
References 30 publications
(44 reference statements)
10
212
4
2
Order By: Relevance
“…B-cell-specific gene NALP7 (Supplementary Figure 3b) is a member of a family of pyrin domain proteins with some members implicated in inflammatory signalling. 68 LOC220213 is in only bone marrow plasma cells and FLJ23235 is also expressed in plasma cells from blood. KIAA1384 is specifically and highly expressed only in blood plasma cells (Figure 3c).…”
Section: Discussionmentioning
confidence: 99%
“…B-cell-specific gene NALP7 (Supplementary Figure 3b) is a member of a family of pyrin domain proteins with some members implicated in inflammatory signalling. 68 LOC220213 is in only bone marrow plasma cells and FLJ23235 is also expressed in plasma cells from blood. KIAA1384 is specifically and highly expressed only in blood plasma cells (Figure 3c).…”
Section: Discussionmentioning
confidence: 99%
“…41 For most of them, the function of Nalps remains unknown. Two Nalp family members, Nalp6 (Pypaf5) 120 and Nalp12 (Pypaf7 or Monarch-1) 121 have been shown to activate the NF-kB pathway. However, others have reported that Monarch-1 dampens NF-kB signals triggered by TLRs or TNF stimulation.…”
Section: Nalpsmentioning
confidence: 99%
“…A more recent proposal suggests the name NACHT-LRR or NLR [9]. Several others reported on the pyrin-containing subgroup or members of this subgroup, which were given various names including PAN, PYPAF and NALP [10][11][12].…”
Section: The Caterpiller (Clr) Gene Familymentioning
confidence: 99%